Implementation Aspects of Search Functionality Over Encrypted Cloud Data - Jivanyan , Aram H.; Hovsepyan , Mihran M. (Mathematical Problems of Computer Science, 2021)
Searchable encryption allows the user to store his data in untrusted environment such as public cloud storages in encrypted form but still be able to access the data via search. Meantime preventing the storage provider to learn either the data or even the search queries. The importance of such functionality raised with the wide adoption of public cloud storages such as Dropbox or Google Drive and this discipline gained high attention from research community. However, there is no practical application of searchable encryption functionality in industry. In this paper we introduce a novel cloud encryption gateway the goal of which is to protect users data in Dropbox and Google Drive without compromising the usability of those services and particularly providing search functionality over the encrypted data.